OUTCOME OF OPERATED PATIENTS PRESENTING WITH FLOATING KNEE INJURIES AT A TERTIARY CARE HOSPITAL, KARACHI (The Research of Medical Science Review, 2025)
Objective: To evaluate the epidemiology, management strategies, and functional outcomes of floating knee injuries in a tertiary care hospital setting. Place and Duration of Study: Department of Orthopedics, JPMC, Karachi for a duration of six months after approval of synopsis. Methodology: A total of 63 patients with floating knee injuries were included. Patient demographics, injury mechanisms, surgical interventions, and functional outcomes were analyzed. Fraser’s classification was used to categorize injuries, and Karlström and Olerud criteria assessed postoperative recovery. Fixation methods for femur and tibia fractures included intramedullary nailing, plate fixation, and external fixation. Early and late complications, weight-bearing status, range of motion, and radiological union at six months were evaluated. Data were analyzed using descriptive statistics. Results: The majority of patients (42.9%) were aged 15-30 years, with male predominance (77.8%). Road traffic accidents were the leading cause (65.1%). Type I fractures were most common (39.7%), and intramedullary nailing was the preferred fixation method for femur (60.3%) and tibia (55.6%). Early complications occurred in 30.2% of patients, including infection (11.1%) and non-union (9.5%). At six months, 50.8% achieved a normal gait, 61.9% had complete radiological union, and 34.9% showed good functional outcomes. Conclusion: Floating knee injuries primarily affect young males due to high- energy trauma. Early surgical intervention and appropriate fixation methods improve functional outcomes. However, complications remain significant, necessitating improved trauma care and rehabilitation services, particularly in resource-limited settings like Pakistan.